2002
DOI: 10.1021/jp020382q
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Nucleation Rates from Molecular Dynamics Simulations

Abstract: The goal of this research is to develop a reliable method to derive nucleation rates and time lags from times of nucleation observed in sets of molecular dynamics simulations of supercooled clusters undergoing spontaneous freezing. What is taken explicitly into account, which was missing in prior analyses, is the kinetics of transient nucleation. Failure to consider this aspect of nucleation has led to substantially larger errors than the statistical errors associated with the stochastic process. It is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Changing the threshold volumes where nucleation is assumed to have occured does change the estimated nucleation rates somewhat, but the overall trends observed were not greatly impacted by these threshold values. To obtain nucleation rates, we consider that the N 0 different simulation boxes with volumes V box are parts of a larger volume V. [30][31][32][33] When a nucleation event occurs in a simulation box, the volume available for nucleation decreases to V-V box . The rate of change of the number of simulation boxes that have not yet nucleated ͑N͒ is given by…”
Section: B Nucleation Times and Ratesmentioning
confidence: 99%
“…Changing the threshold volumes where nucleation is assumed to have occured does change the estimated nucleation rates somewhat, but the overall trends observed were not greatly impacted by these threshold values. To obtain nucleation rates, we consider that the N 0 different simulation boxes with volumes V box are parts of a larger volume V. [30][31][32][33] When a nucleation event occurs in a simulation box, the volume available for nucleation decreases to V-V box . The rate of change of the number of simulation boxes that have not yet nucleated ͑N͒ is given by…”
Section: B Nucleation Times and Ratesmentioning
confidence: 99%
“…To account for the appreciable statistical uncertainties associated with the stochastic nature of the hypothetical nucleation events when 0 is small, a weighted least-squares procedure was carried out to determine and 0 . Details are given in our previous report [8]. Figure 2 displays images of a nanoparticle at various times during the annealing run from one of the 18 particles with different thermal histories.…”
Section: Estimation Of Recrystallization Ratementioning
confidence: 99%
“…Although the study of the freezing of glasses offered the most direct way to characterize transient nucleation, in principle, analyses of the problem indicated that thousands of independent stochastic data points ͑sets of times at which nuclei materialize͒ are needed to yield a statistically reliable portrayal of the transient regime. 13,14 Such large sets of data have yet to be generated in laboratory experiments. The need for such a large number of points is mainly due to the correlation between the three principal parameters to characterize the transient regime ͑see below͒.…”
Section: Introductionmentioning
confidence: 99%